The effects of psychosocial and economic factors on the quality of life of patients with end-stage renal disease and their caregivers in Klang Valley, Malaysia: protocol for a mixed-methods study - Norhayati Ibrahim; Sin Yee Chu; Ching Sin Siau; Noh Amit; Rozmi Ismail; Abdul Halim Abdul Gafor (BMJ Open)
Introduction The number of patients in Malaysia requiring dialysis is expected to rise substantially in the future due to the ageing population and increasing prevalence of diabetes mellitus and hypertension. Hence, more individuals will be expected to adopt the role of caregivers in the future. The upward trend of end-stage renal disease (ESRD) and caregiving for dialysis patients has detrimental consequences for both patients and caregivers in terms of their psychological well-being and quality of life. Despite the current circumstances, there are very few studies in Malaysia that have explored the psychosocial factors, specifically on the economic impact of the management of ESRD.Methods and analysis This two-phase sequential explanatory mixed-methods design, incorporating a quantitative design (phase I) and a qualitative study (phase II), is to be conducted in 4 government hospitals and 10 other non-governmental organisations or private dialysis centres within Klang Valley, Malaysia. A cross-sectional survey (phase I) will include 236 patient-caregiver dyads, while focus group discussions (phase II) will include 30 participants. The participants for both phases will be recruited purposively. Descriptive statistics, independent sample t-tests and multiple regression analysis will be used for analyses in phase I, and thematic analysis will be used in phase II.Ethics and dissemination Approval for the study has been obtained from the National Medical Research and Ethics Committee (MREC) (NMRR-21-1012-59714) and the Research Ethics Committee of Hospital Canselor Tuanku Muhriz UKM (UKM PPI/111/8/JEP-2021–078) and University of Malaya Medical Centre (MREC ID NO: 2 02 178–10346). Informed consent of the participants will be obtained beforehand, and no personal identifiers will be obtained from the participants to protect their anonymity. The findings will be published in peer-reviewed scientific journals and presented at national or international conferences with minimal anonymised data.